Assessment of in‐utero venlafaxine induced, ROS‐mediated, apoptotic neurodegeneration in fetal neocortex and neurobehavioral sequelae in rat offspring. Issue Volume 40:Issue1(2015:Feb.) (13th November 2014) - Singh, Manish; Singh, K.P.; Shukla, Shubha; Dikshit, Madhu
Abstract: Venlafaxine (VEN), a serotonin and noradrenaline reuptake inhibitor is being used as a drug of choice for treating clinical depression even during pregnancy. It is an important therapeutic option in the treatment of perinatal depression, but the effects of VEN on fetus and the newborn are uncertain. Therefore, present study was undertaken to investigate the safety of in‐utero exposure to VEN in terms of developmental neurotoxicity and neurodegenerative potential by using prenatal rat model. The selected doses of VEN (25, 40 and 50 mg/kg) were administered to pregnant rats from GD 5 to 19 through oral gavage. The fetal brains were dissected and processed for histopathological measurements of neocortical thickness that showed significant reduction. Considering vulnerability of immature brain to free radical injury, VEN exposed neocortices were tested for reactive oxygen species (ROS) levels which were significantly increased. As ROS play important role in the initiation of apoptotic mechanisms, we explored for in situ detection of apoptosis by confocal microscopy that showed enhanced apoptosis including chromatin condensation which was further reconfirmed by electron microscopy. Substantially increased levels of pro‐apoptotic protein Bax and decreased levels of anti‐apoptotic protein Bcl2 as shown by western blotting also supported the increased neuro‐apoptotic degeneration. For further correlation of these findings, prenatally VEN exposed young‐adult rat offspring were assessed for open field exploratory behavior that showed increased anxiety‐like and stereotypic responses indicating disturbed neurobehavioral pattern. The study concludes that prenatal VEN exposure may primarily enhance ROS generation that plays a key role in regulating release of proapoptotic factors from mitochondria and thereby enhancing apoptotic neurodegeneration that affect proliferation, migration and differentiation of cells, resulting in neuronal deficits manifested as long term neurobehavioral impairments.